Inferências conceituais em idosos com idosos com e sem Alzheimer - Toscano, Mábia Nunes (2013)
This Master's thesis aims at investigating the inferential comprehension in elderly subjects with and without Alzheimer's disease, as well as, the interference of imagery aid in facilitating comprehension. Our general hypothesis is that the subjects would differ between the frequency of errors in the association of phrases of understanding of linguistic inputs with literal and metaphorical structure , and that the introduction of a visual aid is a factor which will facilitate the comprehension of sentences by the individuals. To test this assumption we elaborate two experiments in order to check the general hypothesis out. In the first experiment subjects were exposed to nine sentences with three stimulis metaphorical conventional, three stimulis metaphorical unconventional and three literals, then the participants were asked to relate the meaning of these stimulis emerged with three types of inferences proposed , an inference would be metaphorical, other with literal meaning and other one which the inference could not be related with input presented . In the three stimuli literal inferences were organized to be a plausible reading , another implausible , but with a vocabulary related to the input and the third went beyond the limits of the possible readings . The experiment 1 was applied without using an imagery aid and the experiment 2 with the image which was related to the direction of the stimulus language to be displayed . The research subjects were chosen with 60 years old or more, at least 8 years of schooling . We selected four elderly without Alzheimer and two with Alzheimer’s disease all of them with corrected vision. Anchored in the Conceptual Integration Theory, whose the main contributions provide theoretical tools that allow researchers to understand the development of human thought , we analyzed the experimental conditions metaphorical in order to demonstrate what kind of abstractions are made when interpreting such structures both conventional and non-conventional ones . Regarding the results of the tests , we can conclude that in the first experiment when were presented an imagine preceding the linguistic input, the frequency of errors in associating literals conditions to sentences of understanding by the general population research was not significant but became relevant when we included an image as " preparation " for reading . On the other hand, when the image was displayed there was no significant differences in the frequency of errors in subjects with Alzheimer's in the understanding metaphoric terms , and when there was pictorial aid , this frequency errors become significant . Perhaps in this case the image may have acted as a facilitator , but it will be necessary to develop other tests that can more accurately assess the influence of imagery support in understanding Alzheimer's patients.